Profile of Food Intake and Physical Activity in Ar-Rahman Drugs Rehabilitation Center Review of Nutritional Status - Deswantoro, Oka Agil; Hartati, Hartati; Iyakrus, Iyakrus; Usra, Meirizal; Utama, Sukma (Department of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this study was to find out how food consumption and physical activity of drug rehabilitation patients Ar-Rahman Palembang were assessed from nutritional status. Using descriptive qualitative method. The population of this study were all AR-Rahman Palembang drug rehabilitation patients, totaling 32 respondents. Data collection techniques used are questionnaires, interviews, nutritional status application software and documentation. With the results of food intake, namely 9.38% of respondents in the very low category, 9.38% in the low category, 59.38% in the medium category, then 21.88% of the respondents in the high category. The results of physical activity are 12.50% of respondents in the very low category, 12.50% of the respondents in the low category, 34.38% of the respondents in the medium category, then 40.63% of the respondents in the high category. The nutritional status of respondents 9.38% belongs to the very poor category, 25.00% belongs to the less category, 28.13% belongs to the medium category. 34,38 % belong to good category. 3.13% classified as very good category. The conclusion from the results of the majority of food intake is in the low category, the results of the majority of physical activity are in the high category and the results of the nutritional status of the Ar-Rahman drug rehabilitation patients are in the moderate category. From these results, so that it can be a further reference for all patients, they can increase their food consumption for the better, always do physical activity every day on a regular basis so that the nutritional status category of patients can be improved for the better.